Alarm state in the Spanish constitutional system: Air space (Acta Judicial Journal, 2018)
The alarm state is configured as one of the so-called emergency states envisaged in the vast majority of the countries in our environment and that are established to respond to certain extraordinary events that, in some way, can produce a serious disturbance of constitutional normality. In the Spanish Constitution of 1978, these defense mechanisms have been established in articles 55 and 116. The first contemplates the possibility of suspending certain rights, and the second refers to the typology of exceptional situations (states of alarm, emergency and siege). With regard to the alarm state, it has only been declared on one occasion that took place as a result of the closure of the airspace that took place due to the strike of air traffic controllers, giving rise to Royal Decree 1673/2010.
Keywords: Alarm state, Right of emergency, States of emergency, Strike, Air traffic controllers.